Pengawasan Badan Permusyawaratan Desa (BPD) terhadap Kinerja Kepala Desa Balokang Kecamatan Banjar Kota Banjar - Asep Nurdin Rosihan Anwar; Rifal Amalindi; Ergun Alfauzi; Ersa Mitha A; Muhammad Aditya Ramdhani; Sari Nurhayati; Yoga Gustiadi (Pusat Riset dan Inovasi Nasional, 2024)
This research is motivated by a lack of knowledge regarding the main tasks and functions, as well as a lack of effectiveness in monitoring the performance of the village head, so that monitoring the village head does not go according to what the community expects and there is a lot of chaos that occurs due to factors caused by village government and the absence of sharper movements in resolving problems that occur in society. The aim of this research is to determine the supervision of the Village Consultative Body (BPD) on the performance of the Head of Balokang Village, Banjar District, Banjar City. The method used in this research is a descriptive qualitative research method. Data collection techniques include: Interview observation and documentation. The data processing techniques in this research are: Data collection, data reduction, data presentation and conclusion drawing/verification. The informants in this research were 3 (seven) people. Based on the research results, it is known that the Village Government Performance Monitoring by the Village Consultative Body (BPD) in Balokang Village, Banjar District, Banjar City in carrying out work direction has not carried out its role well. So it is difficult for the village government to get input and direction regarding needs that are considered priority needs for the village. In determining the work standards of the Village Consultative Body (BPD) it has not been implemented effectively, this is proven by the lack of understanding by members of the BPD of Balokang village, Banjar sub-district, Banjar city of the existing guidelines for setting work standards carried out by the village head. Lack of supervision in observing the course of operational activities on a regular basis, this has resulted in irregularities committed by unscrupulous village officials. The ability of BPD members to report regularly is still lacking. Because understanding of the main duties and functions of each member has not been implemented properly, the performance of the Balokang village government tends to be slow.